2022
DOI: 10.1128/mbio.03814-21
|View full text |Cite
|
Sign up to set email alerts
|

Two Polyketides Intertwined in Complex Regulation: Posttranscriptional CsrA-Mediated Control of Colibactin and Yersiniabactin Synthesis in Escherichia coli

Abstract: Secondary metabolite expression is a widespread strategy among bacteria to improve their fitness in habitats where they constantly compete for resources with other bacteria. The production of secondary metabolites is associated with a metabolic and energetic burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 99 publications
2
17
0
Order By: Relevance
“…These BGCs are present across diverse genera like Escherichia , Klebsiella , Enterobacter , and Citrobacter . Recent studies have shown a tight correlation between colibactin and yersiniabactin evolution and expression [ [37] , [38] , [39] , [40] ]. The yersiniabactin BGC is observed to be present whenever colibactin is present across genera as also seen earlier [ 41 ], with exception of E. coli BCE049 and K. pneumoniae 11492 that only contained colibactin BGC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These BGCs are present across diverse genera like Escherichia , Klebsiella , Enterobacter , and Citrobacter . Recent studies have shown a tight correlation between colibactin and yersiniabactin evolution and expression [ [37] , [38] , [39] , [40] ]. The yersiniabactin BGC is observed to be present whenever colibactin is present across genera as also seen earlier [ 41 ], with exception of E. coli BCE049 and K. pneumoniae 11492 that only contained colibactin BGC.…”
Section: Resultsmentioning
confidence: 99%
“…The gene ripA_2 is associatively present in all colibactin-containing strains along with the known transcriptional regulator ybtA of the AraC-like family. The ybtA gene expression is shown to be required under iron limiting conditions to initiate expression polyketides [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been repeatedly reported that DNA damage was observed in enterocytes of rats and mice colonized or force-fed with different strains of E. coli pks+ (NC101, 192PP, M1/5, SP15, Nissle 1917) (13,15,16,18,39). Keeping in mind that colibactin production is also regulated by numerous environmental cues such as iron, polyamines, and carbon sources (20)(21)(22), the physiological hypoxia at the surface of the epithelium could constitute a favorable environment for colibactin production and activity. Other low oxygen intestinal compartments could favor colibactin production, such as the stem cells that reside in a hypoxic niche (as low as 1% O2) at the bottom of the crypt (40).…”
Section: Discussionmentioning
confidence: 99%
“…The assay was performed as previously described [39]. Briefly, linearized plasmid DNA was generated by digestion of pUC19 plasmid with BamHI (New England Biolabs).…”
Section: Methodsmentioning
confidence: 99%